REENGINEERING OF THE AIR SIMULATORS LEGACY SOFTWARE - Sidorov, Nikolay O.; Khomenko, Vladimir A.; Nedovodeev, Viktor T. (Proceedings of National Aviation University (archive), 2008)
There are the technical complexes consisting of components, parts of which are actively used, but the rest has lost working capacity owing to moral and physical deterioration. An example of such a complex is the aviation-flight complex "plane-simulator". High cost of components which continue to be used (plane) do the actual task of restoring and supporting the out-of-order components (simulator). The considerable part of such complexes is the software, which owing to replacement of the obsolete and physically worn out hardware requires the rework. The rework method is reengineering.